2007
DOI: 10.1136/oem.2007.033423
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, work ability, and self employment: a population survey of entrepreneurs, farmers, and salary earners

Abstract: Farmers have poorer work ability, QoL, and HRQoL than other working groups, but this does not appear to be caused by physical health problems. From a research point of view, farmers should be categorised separately from other forms of entrepreneurship. From a public health point of view, improving farmers' wellbeing may require psychosocial interventions exceeding traditional health promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 35 publications
(34 reference statements)
3
30
0
Order By: Relevance
“…By contrast, studies conducted by Parslow et al (2004), Binder and Coad (2013), and Saarni et al (2008), women, entrepreneurs with employees, farmers, and necessity versus opportunity entrepreneurs demonstrated elevated mental and/or physical health challenges compared to other self-employed people. Entrepreneur MWB research has not evaluated how diagnosable psychiatric conditions might make entrepreneurs more at risk or more resilient.…”
Section: Entrepreneur Mental Health and Well-beingmentioning
confidence: 79%
“…By contrast, studies conducted by Parslow et al (2004), Binder and Coad (2013), and Saarni et al (2008), women, entrepreneurs with employees, farmers, and necessity versus opportunity entrepreneurs demonstrated elevated mental and/or physical health challenges compared to other self-employed people. Entrepreneur MWB research has not evaluated how diagnosable psychiatric conditions might make entrepreneurs more at risk or more resilient.…”
Section: Entrepreneur Mental Health and Well-beingmentioning
confidence: 79%
“…Thus, identity is linked with individual farmers' well being. In a recent study by Saarni et al (2007) Finnish farmers were found to have a poorer quality of life and work ability than other entrepreneurs and salary workers, a finding which they concluded as reflecting the ''low control, low support, and high demand'' nature of current Finnish farming. This situation could also be interpreted as farmers' view of themselves (identity) as not being compatible with external demands and expectations.…”
Section: Theories Of Identitymentioning
confidence: 92%
“…However, they may pay a high price in terms of work-related risks of injury and disease, quality of life, access to health care, and overall health status, including higher rates of musculoskeletal pain and disabling discomfort (Saarni et al, 2007;NIOSH, 2006). For example, an average of 700 individuals from the farming and ranching workforce lose their lives annually, and another 120,000 are temporarily or permanently disabled (National Safety Council, 2007).…”
Section: Introductionmentioning
confidence: 98%